Preparation and purification of recombinant outer surface protein A (rOspA) of Borrelia burgdorferi sensu stricto and Borrelia afzelii - Běláková, Jana; Křupka, Michal; Šebestová, Martina; Tuháčková, Jana; Vrzal, Vladimír; Raška, Milan; Weigl, Evžen (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2005)
The recombinant Outer surface protein A (rOspA) from Borrelia burgdorferi is a possible immunogen for protection of infected humans and animals against development of Lyme borreliosis (Lyme disease), a chronic tick-borne disease characterised by diverse dermatologic, neurologic, rheumatic, and cardiac manifestations. For several years, research and development have been directed towards a vaccine for the prevention of this debilitating disease. Numerous animal studies demonstrate that pre-existing antibodies against the outer surface proteins of B. burgdorferi can prevent infection and disease caused by this organism. In this communication, using recombinant DNA technology, genes from B. burgdorferi sensu stricto and B. afzelii were inserted into E. coli-expression vectors and the rOspA were produced. Our aim was to obtain rOspA protein in a purity and quantity desirable for immunization of experimental animals. rOspA is currently the most developed, molecularly-defined vaccine candidate for the prevention of Lyme borreliosis.
Keywords: Genetic Vectors; proteiny vnější bakteriální membrány; Vaccines, DNA; Escherichia coli; Borrelia burgdorferi Group; Borrelia burgdorferi komplex; Antigens, Surface; lipoproteiny; genetické vektory; Bacterial Outer Membrane Proteins; Bacterial Vaccines; Lipoproteins; Borrelia burgdorferi; DNA vakcíny; Lyme Disease Vaccines; antigeny povrchové; vakcína proti lymeské nemoci; bakteriální vakcíny